The Influence of Health Education on the Interest of TM III Pregnant Women in Screening for Congenital Hypothyroidism in Newborn Babies - Darmawan, Shalsabila Febryanti; Hartati, Dwi; Sulistyorini, Chandra; Risnawati, Risnawati (Journal of Midwifery and Nursing, 2024)
Congenital hypothyroidism screening is a screening to select babies who suffer from congenital hypothyroidism from babies who are not sufferers by taking 2-3 drops of blood from the baby's heel. A preliminary study at PMB Midwife Endang in December 2023 found data on the number of normal births of 32 people who underwent congenital hypothyroidism screening with 11 people. It shows that mothers still have low interest in doing Congenital hypothyroidism screening because, on average, they do not know about Congenital hypothyroidism screening, so they are less motivated. Mothers have never been given health education about Congenital hypothyroidism screening. This study aimed to determine the influence of health education on the interest of the third semester of pregnant women in screening for congenital hypothyroidism in newborns. This study used Pre-experimental with one group pre and post-test design. The population was 36 in the third semester of pregnant women at PMB Endang Yuniyati Napitupulu in January, with a sample of 30 people taken using a total sampling technique. The instrument was a questionnaire. Data analysis used the Wilcoxon test. This study showed that before being given health education, most respondents were not interested in doing congenital hypothyroidism screening on their babies (73.3%), and after being given health education, most respondents were interested in doing Congenital hypothyroidism screening on their babies (76.7% ). There was an influence of health education on the interest of the third-semester of pregnant women in screening for congenital hypothyroidism in newborns (p-value = 0.000 < ?: 0.05).